Confronting model misspecification in macroeconomics - Daniel F. Waggoner; Tao Zha (Federal Reserve Bank of Atlanta, 2012)
We estimate a Markov-switching mixture of two familiar macroeconomic models: a richly parameterized dynamic stochastic general equilibrium (DSGE) model and a corresponding Bayesian vector autoregression (BVAR) model. We show that the Markov-switching mixture model dominates both individual models and improves the fit considerably. Our estimation indicates that the DSGE model plays an important role only in the late 1970s and the early 1980s. We show how to use the mixture model as a data filter for estimation of the DSGE model when the BVAR model is not identified. Moreover, we show how to compute the impulse responses to the same type of shock shared by the DSGE and BVAR models when the shock is identified in the BVAR model. Our exercises demonstrate the importance of integrating model uncertainty and parameter uncertainty to address potential model misspecification in macroeconomics.
Keywords: C52; E2; E4; 330; Markov-switching mixture; heterogenous models; regime-dependent weights; model uncertainty; parameter uncertainty; impulse responses; policy analysis; Makroökonomik; Modellierung; Risiko; Theorie